2013
DOI: 10.1111/jre.12105
|View full text |Cite
|
Sign up to set email alerts
|

Gingival crevicular fluid levels of human beta‐defensin‐2 and cathelicidin in smoker and non‐smoker patients: a cross‐sectional study

Abstract: Epithelial cells in contact with microorganisms release LL-37 and hBD-2 to eliminate them. The release response of LL-37 and hBD-2 formed against microorganisms can change depending on factors such as smoking, which activates the nicotinic receptors present on epithelial surfaces. This interaction can increase the release of LL-37 and hBD-2. Smoking may also affect the capillary tissues and reduce leukocytic chemotaxis. The increased number of colonized microorganisms may lead to higher levels of LL-37 and hBD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 55 publications
(66 reference statements)
0
27
0
Order By: Relevance
“…Several in vitro studies have determined that smoking can affect the expression of AMPs in gingival epithelial cells or skin keratinocytes (Table ). Besides, some cross‐sectional, in vivo studies have sought to identify the effect of smoking or nicotine use on AMP expression in saliva or gingival crevicular fluid of periodontitis patients (Table ). The net effect of smoking on AMP expression in the gingival or salivary niches in periodontitis subjects seems to be complicated and remains unclear, chiefly, as the literature in this regard has addressed different natures of target AMPs (human neutrophil peptides [HNP, alpha‐defensins], human beta defensins [HBD] or LL‐37) and oral sample types (gingival crevicular fluid, saliva or tissue).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several in vitro studies have determined that smoking can affect the expression of AMPs in gingival epithelial cells or skin keratinocytes (Table ). Besides, some cross‐sectional, in vivo studies have sought to identify the effect of smoking or nicotine use on AMP expression in saliva or gingival crevicular fluid of periodontitis patients (Table ). The net effect of smoking on AMP expression in the gingival or salivary niches in periodontitis subjects seems to be complicated and remains unclear, chiefly, as the literature in this regard has addressed different natures of target AMPs (human neutrophil peptides [HNP, alpha‐defensins], human beta defensins [HBD] or LL‐37) and oral sample types (gingival crevicular fluid, saliva or tissue).…”
Section: Resultsmentioning
confidence: 99%
“…HBD‐2 expression has been associated with proinflammatory stimulation such as that from bacterial lipopolysaccharides (LPS) . HBD‐2 levels are shown as significantly higher in smokers with generalized aggressive periodontitis as compared with non‐smokers and similarly higher in smokers with gingivitis when compared to non‐smokers with gingivitis . In addition, HBD‐2 levels in non‐inflamed gingival tissues were shown to be significantly reduced in smokers compared with non‐smokers .…”
Section: Resultsmentioning
confidence: 99%
“…Another study suggested that the pre-treatment with nicotine reduced a stimulating effect of TNF-α on the gene expression of hBD-2 in HaCaT keratinocytes [47]. It was found that hBD-2 protein level in gingival crevicular fluid was significantly higher in smoker patients with gingivitis than that of non-smoker patients with gingivitis, while hBD-2 level in the gingival crevicular fluid was significantly higher in smoker patients with generalized aggressive periodontitis than that of non-smoker patients with generalized aggressive periodontitis [48]. It was reported that whole cigarette smoke exposure up-regulated hBD-2 and hBD-3 [10].…”
Section: Discussionmentioning
confidence: 81%
“…The diagnosis of AR was made according to the Allergic Rhinitis and its Impact on Asthma (ARIA) guidelines (10). Patients who had chronic disease including doctor-diagnosed asthma, whose family members were smokers, and who were using medication including vitamins were not included in the study, because some publications reported that use of vitamins and exposure to smoking affected BD-2 levels (11,12). Twenty-four healthy children who were being followed up in the Outpatient Clinic of Healthy Children and had no known problems, whose parents did not smoke, and who were not using medication were included as the control group.…”
Section: Methodsmentioning
confidence: 99%